Response to Mastrofski and Uchida - Fyfe, James J. (Journal of research in crime and delinquency, 1993)
The authors comment on a review by Stephen D. Mastrofski and Craig D. Uchida of the book Above the Law. They agree with the reviewers' claim that the book does not prescribe broad programs to transform the underlying race, cultural and social class schisms that lie at the root of the problem concerning the use of excessive force by police. However, they argue against the claim that Above the Law does not define excessive force. They provide a definition of brutality and unnecessary force